Behavioral dimensions of user movement in daylit library spaces: a review - Ahmadi, Mosleh; Martyniuk-Pęczek, Justyna; Kostrzewska, Małgorzata; Sokół, Natalia (Budownictwo i Architektura / Civil and Architectural Engineering, 2026)
This paper analyzes literature on user movement in libraries within the context of daylighting studies, highlighting its significance for library design in relation to daylighting. The objective is to analyze how library user movement has been addressed in daylighting research. The methodology involves a review of literature utilizing the Scopus and Web of Science (WOS) databases focusing on ’library’ and ’daylight’. It identifies four main categories of user movement in daylighting studies: User Experience and Spatial Utilization, Dynamic User Positions and Spatial Locations, Walking and Transition, and Occupation Over Time. This approach enhances the understanding of user dynamics in libraries, informing design strategies to optimize user experience. The relationship between user movement and daylighting includes parameters like spatial utilization, dynamic positions, walking patterns, and temporal occupation. It identifies a research gap: insufficient studies on physical interactions with daylighting elements and their potential disruptive effects within libraries. The study concludes by defining library user movement in daylighting studies, identifying spatial exploration, user location choices, movement of others, and temporal movement evolution, impacting user satisfaction, visual comfort, and interactions within library spaces.